METHOTREXATE MAY BE AN ALTERNATIVE TO AZATHIOPRINE IN NEUROMYELITIS OPTICA WITH AQUAPORIN-4 ANTIBODIES. (29th November 2012) - Kitley, J; Elsone, L; George, J; Jacob, A; Leite, MI; Palace, J
Abstract : Background: Neuromyelitis optica (NMO) is a severe inflammatory disorder of the central nervous system. In the majority of patients, the disease is associated with pathogenic antibodies to aquaporin-4 (AQP4) and is recurrent. Treatment is aimed at relapse prevention. Azathioprine is often used first line but does not work in all patients and is often not tolerated. Alternative treatments are needed. Methotrexate is a folate antagonist used widely in rheumatoid arthritis, psoriasis and inflammatory bowel disease. In the UK, it is also used for myasthenia gravis. Methods: We describe our experience of methotrexate in 14 cases of relapsing AQP4 antibody-positive NMO. Results: Eleven patients were females, three were males. Median disease duration prior to initiation of methotrexate was 72 months (range 3–192). Three patients were treatment naïve. The mean number of NMO attacks prior to starting methotrexate was 5.3 and mean pre-treatment annualised relapse rate (ARR) was 2.3. Median duration of treatment was 22 months (range 6–84) and mean ARR during treatment was 0.42. Thirteen patients experienced a reduction in ARR on methotrexate and six of these had no attacks. EDSS stabilised or improved in 11 patients. No serious adverse effects occurred. Conclusion: Methotrexate was well tolerated and reduced relapse rates in the majority of patients and may therefore be a suitable alternative to azathioprine in AQP4 antibody-positive NMO.